Conceptualizing femicide as a human rights violation: state responsibility under international law - Hefti, Angela (Edward Elgar Publishing, 2022)
"This thought-provoking book conceptualizes femicide as a multifaceted human rights violation and proposes state responsibility for group-related risks of violence against women and girls. In doing so, it reassesses the concept of femicide, analysing it in view of the crime of genocide, crimes against humanity, war crimes, as well as several facets of human rights. Angela Hefti challenges the common definition of femicide, extending it beyond the killing of women due to their gender to include elements of victim blame, sexual abuse, forced marriage and delayed investigations by authorities. Chapters address femicide in the context of the African, Inter-American and European regional and universal human rights systems. Case studies from Iraq, Nigeria and Mexico provide a fundamental understanding of the multidimensional and worldwide nature of femicide. Spanning several key academic debates, the book incorporates underlying feminist legal theory and approaches pertaining to the subordination of women and girls in society, arguing that femicide should qualify as an autonomous human rights violation. Providing an impetus for further research on femicide, particularly on state responsibility for crimes committed by private actors, this book will be a crucial resource for academics in human rights and humanitarian law, criminal law and justice. The book will also be highly valuable to activists, practitioners, and lawyers with an interest in advancing aspects of femicide in international human rights law"--